A Systematic Review and Meta-Analysis of Magnetic Resonance Imaging Studies in Late-Life Depression. - Sexton, C; Mackay, C; Ebmeier, K (2012)
Gray matter abnormalities within frontal-subcortical and limbic networks are hypothesized to play a key role in the pathophysiology of late-life depression. In this work, gray matter abnormalities in late-life depression are examined in a systematic review and meta-analysis of magnetic resonance imaging studies. In the systematic review, 27 articles were identified that compared participants with late-life depression with comparison group participants, and 17 studies were suitable for inclusion in meta-analyses of volumes of the whole brain, orbitofrontal cortex, caudate, hippocampus, putamen, and thalamus. Volume reductions were detected in 7 of 15 comparisons of the hippocampus and a meta-analysis revealed a significant, but small, effect size. Although examined by fewer studies, meta-analyses also revealed significant volume reductions in the orbitofrontal cortex, putamen, and thalamus. A more systematic and comprehensive analysis of the global distribution of gray matter abnormalities, and an examination of subcortical abnormalities were identified as key areas for future research.